Synoptic-Dynamic Meteorology and Weather Analysis and Forecasting A Tribute to Fred Sanders - Bosart, Lance; Bluestein, Howard (Meteorological Monographs ;, 2008)
This long-anticipated monograph honoring scientist and teacher Fred Sanders includes 16 articles by various authors as well as dozens of unique photographs evoking Fred's character and the vitality of the scientific community he helped develop through his work. Editors Lance F. Bosart (University at Albany/SUNY) and Howard B. Bluestein (University of Oklahoma at Norman) have brought together contributions from luminary authors-including Kerry Emanuel, Robert Burpee, Edward Kessler, and Louis Uccellini-to honor Fred's work in the fields of forecasting, weather analysis, synoptic meteorology, and climatology. The result is a significant volume of work that represents a lasting record of Fred Sanders' influence on atmospheric science and legacy of teaching.